First Report of Garlic virus B and Garlic virus D in Garlic in the Pacific Northwest - Gieck, S L (Plant disease, 2009)
With the recent report of several viruses infecting garlic (Allium sativum L.) grown in the Pacific Northwest (1-3), studies were initiated on cloves planted in the fall of 2006 to determine the presence of additional viruses infecting plants exhibiting mosaic and/or chlorotic leaves. Cloves from symptomatic plants of the cultivar 'Early' from two seed production fields in Benton County, WA and two seed production fields in Morrow County, OR were tested by two-step reverse transcription (RT)-PCR using primers specific to the coat protein (CP) of the allexiviruses (4), since garlic infected with this group had similar symptoms in Asia and South America (4). Of the 87 cloves tested, 84 were positive, and four representative samples of the RT-PCR amplicons from each location were cloned and sequenced. Sequence comparisons indicated that the cloves from both locations were infected with Garlic virus D (GarV-D), also known as Japanese garlic virus (JGV), since they shared 98% identity with known isolates (GenBank Accession Nos. L388922.1, AF519572.1, and AB010303.1). In addition, sequences of isolates from the Oregon cloves shared a 96% identity with a known isolate of Garlic virus B (GarV-B; GenBank Accession No. AF543829.1). Because no antiserum specific to these viruses was available, primers specific to the CP genes of GarV-D (JGV-F2/JGV-R2 5'-GCTCACTCRGATGTGTTAGC-3' and 5'-CGCGTGGACATAAGTTGTTG-3') and GarV-B (GVB-F1/GVB-R2 5'-GAGGAGAACTAACGCCACAC-3' and 5'-ACGACCTAGCTTCCTACTTG-3') were designed and the cloves were retested by RT-PCR using these virus-specific primers. With the GarV-D specific primers, 98 and 63% of the cloves were positive from Washington and Oregon, respectively, and 52% of the cloves from Oregon were positive using the GarV-B specific primers. None of the cloves tested from Washington were positive for GarV-B. The identity of the amplicons was verified by cloning and sequencing (GarV-D, GenBank Accession No. FJ643476; GarV-B, GenBank Accession No. FJ643475). Incidence of the two viruses differed between Oregon and Washington was likely due to the expansion of the seed lots in two different locations (California and Nevada) prior to planting in 2006. With such high infection rates, studies should be conducted to determine the impact of these viruses on yield when plants are singly infected as well as in combination with the other viruses known to infect garlic in this region. These and the other viruses (1) are likely to impact yield. To our knowledge, this is the first report of GarV-D (JGV) and GarV-B in garlic in the Pacific Northwest. References: (1) S. L. Gieck et al. Plant Dis. 91:461, 2007. (2) H. R. Pappu et al. Plant Dis. 89:205, 2005 (3) H. R. Pappu et al. Online publication. doi:10.1094/PHP-2008-0919-01-RS. Plant Health Progress, 2008. (4) T. Tsuneyoshi et al. Phytopathology 86:253, 1996